2020
DOI: 10.5334/aogh.2885
|View full text |Cite
|
Sign up to set email alerts
|

Level of Knowledge on Stroke and Associated Factors: A Cross-Sectional Study at Primary Health Care Centers in Morocco

Abstract: Background: Stroke is increasingly becoming a major cause of disability and mortality. However, it can be prevented by raising awareness about risk factors and early health care management of patients. Objective: The aim of this study is to assess the level of knowledge on stroke, its risk factors, and warning signs in the population attending urban primary health care centers in the city of Agadir, Morocco. Methods: This is a multicentric cross-sectional study with a descriptive and analytical purpose. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 42 publications
11
22
0
2
Order By: Relevance
“…Despite being one of the most common modifiable risk factors for stroke, Diabetes Mellitus was relatively less identifiable by our study participants (68.4%). This finding has been reported elsewhere in previous studies ( Kharbach et al, 2020a ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Despite being one of the most common modifiable risk factors for stroke, Diabetes Mellitus was relatively less identifiable by our study participants (68.4%). This finding has been reported elsewhere in previous studies ( Kharbach et al, 2020a ).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, hypertension (48.2%), followed by stress (43.1%), were identified as risk factors among participants in a study from Lebanon (43.1%) ( Khalil and Lahoud, 2020 ). Similarly, among 469 participants in a study from Morocco, hypertension (55.7%), followed by stress (48.8%), were identified as risk factors for stroke ( Kharbach et al, 2020b ). Despite being one of the most common modifiable risk factors for stroke, Diabetes Mellitus was relatively less identifiable by our study participants (68.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol consumption and hypercholesterolemia were the subsequent risk factors identified. This is in agreement with the study done in Morocco where the most frequently identified warning signs and risk factors were sudden weakness of the arm, leg or face and hypertension, respectively ( 25 ).…”
Section: Discussionsupporting
confidence: 92%
“…Hypertensive patients who had secondary education, and above were more than four times more likely to have adequate stroke knowledge. This was concordant with the findings of a range of studies in which high educational level had been the most associated factor with adequate knowledge of stroke in hypertensive patients in Ethiopia ( 26 , 28 , 29 ), and Nigeria ( 14 , 32 ) Morocco ( 25 ), and Beirut ( 33 ). This may be due to the fact that individuals who have a higher educational level may have more interaction with society and have easy access to health-related information from various sources like the internet, news, books, magazines, and literature as compared with individuals who have no formal education, which is supported by the systematic reviews reporting that educational status has a significant impact on cardiovascular disease knowledge in SSA populations ( 24 , 34 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation